The Ile191Val is a partial loss-of-function variant of the TAS1R2 sweet-taste receptor and is associated with reduced glucose excursions in humans - Joan Serrano; Jaroslava Seflova; Jihye Park; Marsha Pribadi; Keisuke Sanematsu; Noriatsu Shigemura; Vanida Serna; Fanchao Yi; Andrea Mari; Erik Procko; Richard E. Pratley; Seth L. Robia; et al. (Elsevier, 2021)
Objective: Sweet taste receptors (STR) are expressed in the gut and other extra-oral tissues, suggesting that STR-mediated nutrient sensing may contribute to human physiology beyond taste. A common variant (Ile191Val) in the TAS1R2 gene of STR is associated with nutritional and metabolic outcomes independent of changes in taste perception. It is unclear whether this polymorphism directly alters STR function and how it may contribute to metabolic regulation. Methods: We implemented a combination of in vitro biochemical approaches to decipher the effects of TAS1R2 polymorphism on STR function. Then, as proof-of-concept, we assessed its effects on glucose homeostasis in apparently healthy lean participants. Results: The Ile191Val variant causes a partial loss of function of TAS1R2 through reduced receptor availability in the plasma membrane. Val minor allele carriers have reduced glucose excursions during an OGTT, mirroring effects previously seen in mice with genetic loss of function of TAS1R2. These effects were not due to differences in beta-cell function or insulin sensitivity. Conclusions: Our pilot studies on a common TAS1R2 polymorphism suggest that STR sensory function in peripheral tissues, such as the intestine, may contribute to the regulation of metabolic control in humans.